AKSELERASI PENGEMBANGAN WISATA BUDAYA BERBASIS PENINGGALAN MEGALITIKUM DESA KAMAL, JEMBER - Hariyadi, Edy; Saputra, Heru S.P.; Maslikatin, Titik; Siswanto; Rato, Dominikus; Ilham, Mochamad; Yuliati, Lilis (PAPUMA: Journal of Community Services, 2024)
This article discusses the development of cultural tourism based on ancient heritage in Kamal Village, Arjasa District, Jember Regency. The problem is the lack of adequate governance and infrastructure to support cultural tourism, as well as the lack of innovative and creative human resources. This community service aims to accelerate the development of cultural tourism through tourism management training, development of infrastructure, and increasing the capacity of the local community. The methods used are observation, problem mapping, and intensive training. The results obtained show an increase in public awareness of the potential for cultural tourism, the arrangement of supporting tourism infrastructure, and the formation of tourism management groups. In conclusion, efforts to develop cultural tourism in Kamal Village need to be continued with the active role of the community and government support to achieve sustainability and improve the village economy.